Run, rose, run ebook A novel. - Patterson, James (2022)
From America’s most beloved superstar and #1 New York Times bestselling author James Patterson comes a thriller about a young singer-songwriter on the rise—and on the run—and determined to do whatever it takes to survive. Every song tells a story.  She’s a star on the rise, singing about the hard life behind her.  She’s also on the run. Find a future, lose a past.  Nashville is where she’s come to claim her destiny.  It’s also where the darkness she’s fled might find her.  And destroy her.  Run, Rose, Run is a novel glittering with danger and desire—a story that only America’s #1 beloved entertainer and its #1 bestselling author could have created.